Implementation of Internet of Things (IoT) in Libraries: Challenges and Opportunities - Gohil Prakashsinh (Journal of Agricultural Extension Management, 2021)
Agriculture forms a significant part of our Indian economy. Agriculture and irrigation are the essential and foremost sectors in the current world. It is a mandatory need to apply information and communication technology in our agricultural industries to aid agriculturalists and farmers in improving all stages of crop cultivation and post-harvest activities. This paper highlights the modern technologies deployed to agriculture, and discusses the challenges and possible solutions and implementations. It proposes an implementation framework for using Internet of Things (IoT) to renovate the conventional library systems to become smart online library schemes. The IoT enables the connectivity of a physical object (such as a book or other text typologies) with real-time communication technology by using RFID tags and tiny sensors. The Internet of Things can also provide a global linking of a considerable number of libraries and universities in real-time, all the time. It is concluded that the IoTbased library management systems will be a good structure that can play a vital role in human data organization and knowledge access by helping researchers, farmers, agriculturalists more efficiently and smartly